Food-based STEAM Learning Activities Reduce Decline in Preschoolers Skin Carotenoid Status - Bayles, Jocelyn (East Carolina University, 2021)
Objective: To assess the effectiveness of food-based Science, Technology, Engineering, Art, Mathematics (STEAM) learning activities on children’s liking of nine target vegetables and overall fruit/vegetable intake. Methods: Seven hands-on, food-based STEAM learning activities to expose children to nine target vegetables in Head Start preschools across North Carolina. Child-reported vegetable liking scores and skin carotenoid status (SCS) were collected at baseline, midpoint, and post-test (Dependent variables = change in child-reported liking scores and SCS; independent variables = sex, age, baseline Body Mass Index, and intervention versus control). Results: A total of 113 children (Intervention =49; Control =64) participated in the study. A time-by-group interaction was not significant for target vegetable liking scores. A time-by-group interaction was significant for SCS. Both groups declined (I=0.06%; C=15.09%) with a smaller decline observed in the intervention group (p= .02). Conclusions and Implications: Food-based STEAM learning activities may present a unique opportunity to impact FV consumption, while meeting academic standards.
Keywords: Food-based Learning; STEAM; Head Start; Preschool; Food Preferences